BUILDING ENERGY MANAGEMENT OPTIMIZATION WITH REINFORCEMENT LEARNING METHOD TO IMPROVE PHOTOVOLTAIC SELF-CONSUMPTION - Puspita, Yumna
The global climate change has prompted the Indonesian government to enhance the electricity energy mix, one of which is through the installation of microgrids in buildings. However, the intermittent nature of PV production can lead to a decrease in grid reliability. Furthermore, from the demand side, electricity consumption profile in university buildings is complex and dynamic, requiring an energy management system in the building. One parameter of building energy management systems is the self-consumption of directly consumed PV production. Therefore, an increase in photovoltaic self-consumption is achieved by implementing energy management control in the building, one of which is through the management of charging and discharging in Battery Energy Storage System (BESS).